A comparative study of oxide scales grown on stainless steel and nickel-based superalloys in ultra-high temperature supercritical water at 800 °C. (May 2016) - Behnamian, Yashar; Mostafaei, Amir; Kohandehghan, Alireza; Amirkhiz, Babak Shalchi; Serate, Dominic; Sun, Yifei; Liu, Subiao; Aghaie, Ermia; Zeng, Yimin; Chmielus, Markus; Zheng, Wenyue; Guzonas, David; et al.
Abstract: This study investigates the oxidation behavior of several stainless steels and nickel-based superalloys exposed to supercritical water at 800 °C for 12 h. Characterization of the resulting oxide layers were conducted using weight change measurements, X-ray diffraction, scanning/transmission electron microscopy, and energy dispersive spectroscopy. Although the exposure time is only 12 h, the thickness of the oxide layers formed was as high as 1 μm, comprising different spinel structures. The influence of alloying elements such as Al, Nb, Mo, Mn and Ti on the corrosion behavior is investigated and possible corrosion mechanisms for each candidate alloy are discussed.